(untitled) (Lapai Journal of Economics, 2020)
Modern organisations are always under the change effort to enhance internal and external organisational operations because of competitiveness in the dynamic business environment. This study investigates the effect of change management strategies on employees’ performance in relation to technological changes, change management strategies and innovation implementation challenges. This study used a samples of 83 employees and data were collected using questionnaire and interview responses. Three (3) hypotheses were postulated and tested with the aid of regression analysis. The result of the three hypotheses revealed that technological up-gradation, changes in management strategies and organizational innovative culture enhances the performance of employees positively. The study concluded that investment in technological innovation, automation of the process, adequate management techniques are necessary prerequisite for the remaining is relevant in the dynamic business environment.